Hair follicle stem cells and the collapse of self-tolerance in alopecia: the interplay of barrier function, the microbiome, and immunity - Joseph S Durgin; Sunny Y Wong (EMBO Molecular Medicine)
The hair follicle is thought to be a site of ‘immune privilege,’ or relative protection from autoimmune and inflammatory responses. In particular, the long-lived, quiescent hair follicle stem cells (HFSCs) are strikingly resistant to cytotoxic immune effectors such as T cells and natural killer (NK) cells, even in systems where these cells are artificially directed to attack HFSCs. Nonetheless, many forms of alopecia are associated with immune-mediated damage of the hair follicle epithelium, suggesting a failure of immune privilege. What precipitates the collapse of HFSC immune privilege in alopecia? In this current issue of EMBO Molecular Medicine, Strobl et al use an innovative mouse model to add to our mechanistic understanding of this disorder (Strobl et al, 2024).